Is Myotis brandtii a fussy little bat? : habitat selection and impact of forestry on Brandt's bat (Myotis brandtii) - Kammonen, Johanna (SLU/Swedish Biodiversity Centre, 2019)
Humans are expanding their land use with e.g. forestry, agriculture and urbanisation, which can have both positive and negative effects upon biodiversity. One taxon that has shown to be affected by forestry is bats, however, the impacts differ depending on forestry method and their foraging strategy. This study focused on the habitat composition around maternity colonies of the forest-living Brandt’s bat (Myotis brandtii) in Sweden, with the objective to investigate how the species might be af-fected by forestry and if their presence of colonies can be predicted based on habitat composition. To do so, bat activity and insect abundance was measured in relation to a number of habitat variables (forest density, canopy cover and level of soil moisture), and in three types of forest habitats (coniferous forest, swamp forest and edge be-tween forest and open areas). Insects were caught with suction traps and bat activity was surveyed with automatic ultrasound detectors. Habitat composition within 1 km radius from 14 colonies was compared to three control areas of 20 × 20 km. Insect abundance and bat activity was not correlated. Insect abundance was highest at edge habitat, while bat activity was highest in swamp forests. High level of soil moisture was important for both insect abundance and bat activity, which suggests that drainage of forests is negative for forest-living bats. There was a trend towards more bats in medium dense forest, which suggests that the species is tolerant towards thinning of forests. Habitat coverage did not differ between colony areas and control areas, and the variance was large in colony areas. This indicates that M. brandtii oc-curs in the dominant type of landscape in the studied area. It was not possible to relate presence of colonies to occurrence or distribution to any habitat, making it hard to predict M. brandtii colony presence based on maps. Forestry methods in which a continuous crown cover is conserved is positive for forest-living bats, but the main conservation measure is to restore or create new forested wetlands.